Foscolo's notes in Gambarin edition of "La chioma di Berenice" (Prassi Ecdotiche della Modernità Letteraria, 2018)
The paper aims at reconstructing the ecdotic criteria used by Giovanni Gambarin in his edition of Foscolo's translation of the Chioma di Berenice by Catullo, and of the related author's annotations (1972). The collation between the edition and the original printing with handwritten notes, preserved in Florence at the Biblioteca Marucelliana (R. E. 151) allows to recognize the figure of a scholar ready to renew the philological practices of his time, introducing the critical apparatus and reintegrating into the work the translation of  the letter to Ortalo, incorrectly expunged by the previous editor.
Keywords: Foscolo; Gambarin; annotations; notes; edition